The Relationship Between Self Efficacy and Mother’s Experience in Assisting Adolescents Using Gadgets - Made Dewi Sariyani; Kadek Sri Ariyanti; Dyah Pradnyaparamitha Duarsa; Nur Fatihah Mutmainah (Nursing and Health Sciences Journal (NHSJ), 2022)
Mother is the closest person to teenagers. In addition to caring, mothers also have the ability to supervise and assist teenagers in using gadgets. Self-efficacy is important in conducting supervision because it is a part of the cognitive competence. Tha purpose knowing the relationship between self-efficacy and mother's experience in assisting adolescents using gadgets. The research method uses quantitative research with 345 teenager mothers in public junior high schools in Denpasar. The result of the study is the most of the informants' mothers still had bad experiences, that is about 243 people (70.4%). The variables that have a significant effect on the dependent variable. DIII education increases the chance of 27 times (AOR = 27.54) the level of mother's efficacy in medium compared to other education. The results show that in general, most mothers still have low efficacy in terms of assisting early teenagerss who use gadgets before intervention. There is a significant positive relationship between mother's experience and mother's self-efficacy in assisting early teens who use gadgets. The suggestions that can be conveyed is Mothers are expected to be able to provide assistance to their children in the use of gadgets